Analysis and Validation of circRNA-miRNA Network in Regulating m6A RNA Methylation Modulators Reveals CircMAP2K4/miR-139-5p/YTHDF1 Axis Involving the Proliferation of Hepatocellular Carcinoma - Chi, Fanwu; Cao, Yong; Chen, Yuhan (Frontiers in Oncology, 2021)
The m6A RNA methylation modulators play a crucial role in regulating hepatocellular carcinoma (HCC) progression. The circular RNA (circRNA) regulatory network in regulating m6A RNA methylation modulators in HCC remains largely unknown. In this study, 5 prognostic m6A RNA methylation modulators in HCC were identified from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) projects. The differentially expressed microRNAs (DEmiRNAs) and circRNAs (DEcircRNAs) between paired tumor and normal tissues were screened out from TCGA and or Gene Expression Omnibus (GEO) database to construct the circRNA-miRNA- m6A RNA methylation modulator regulatory network, which included three m6A RNA methylation modulators (HNRNPC, YTHDF1, and YTHDF2), 11 DEmiRNAs, and eight DEcircRNAs. Among the network, hsa-miR-139-5p expression was negatively correlated with YTHDF1. Hsa-miR-139-5p low or YTHDF1 high expression was correlated with high pathological grade, advanced stage and poor survival of HCC. Additionally, cell cycle, base excision repair, and homologous recombination were enriched in YTHDF1 high expression group by GSEA. A hub circRNA regulatory network was constructed based on hsa-miR-139-5p/YTHDF1 axis. Furthermore, hsa_circ_0007456(circMAP2K4) was validated to promote HCC cell proliferation by binding with hsa-miR-139-5p to promote YTHDF1 expression. Taken together, we identified certain circRNA regulatory network related to m6A RNA methylation modulators and provided clues for mechanism study and therapeutic targets for HCC.